Protocol: Transmission and prevention of influenza in Hutterites: Zoonotic transmission of influenza A: swine & swine workers - Loeb Mark; Moss Lorraine; Singh Pam; Fonseca Kevin; Keenliside Julia; Webby Richard; Russell Margaret L (BMC, 2009)
Abstract Background Among swine, reassortment of influenza virus genes from birds, pigs, and humans could generate influenza viruses with pandemic potential. Humans with acute infection might also be a source of infection for swine production units. This article describes the study design and methods being used to assess influenza A transmission between swine workers and pigs. We hypothesize that transmission of swine influenza viruses to humans, transmission of human influenza viruses to swine, and reassortment of human and swine influenza A viruses is occurring. The project is part of a Team Grant; all Team Grant studies include active surveillance for influenza among Hutterite swine farmers in Alberta, Canada. This project also includes non-Hutterite swine farms that are experiencing swine respiratory illness. Methods/Design Nurses conduct active surveillance for influenza-like-illness (ILI), visiting participating communally owned and operated Hutterite swine farms twice weekly. Nasopharyngeal swabs and acute and convalescent sera are obtained from persons with any two such symptoms. Swabs are tested for influenza A and B by a real time RT-PCR (reverse transcriptase polymerase chain reaction) at the Alberta Provincial Laboratory for Public Health (ProvLab). Test-positive participants are advised that they have influenza. The occurrence of test-positive swine workers triggers sampling (swabbing, acute and convalescent serology) of the swine herd by veterinarians. Specimens obtained from swine are couriered to St. Jude Children's Research Hospital, Memphis, TN for testing. Veterinarians and herd owners are notified if animal specimens are test-positive for influenza. If swine ILI occurs, veterinarians obtain samples from the pigs; test-positives from the animals trigger nurses to obtain specimens (swabbing, acute and convalescent serology) from the swine workers. ProvLab cultures influenza virus from human specimens, freezes these cultures and human sera, and ships them to St. Jude where sera will be examined for antibodies to swine and human influenza virus strains or reassortants. Full length sequencing of all eight genes from the human and swine influenza isolates will be performed so that detailed comparisons can be performed between them. Discussion The declaration of pandemic influenza in June 2009, caused by a novel H1N1 virus that includes avian, swine and human genes, highlights the importance of investigations of human/swine influenza transmission.